Impacts of the Invading Golden Mussel Limnoperna fortunei on Zooplankton: a Mesocosm Experiment - Rojas Molina, Florencia Mercedes (2012)
Invasive filter-feeding mussels and clams are well-known for profoundly impacting the invaded systems. Many studies in South America documented interactions of the Asian mussel Limnoperna fortunei with several components of the local biota. However, few experiments have examined in detail the effect of the mussels on zooplankton abundances and the species composition. We conducted a 72-h experiment to assess the impacts of L. fortunei on the composition and abundance of Paraná River floodplain zooplankton using experimental mesocosms. Three treatments with 3 replicates each were used in the experiment: control (without mussels) and 2 treatments with mussels at different concentrations. Densities of the most abundant genera of rotifers (Keratella) and cladocerans (Bosmina and Diaphanosoma) significantly declined in mollusc-containing mesocosms compared to the control. Phytoplankton density was significantly lower in the presence of the mollusc. Mesocosms with higher mollusc concentrations had lower zooplankton densities than those with fewer predators. Therefore, our results strongly suggest that L. fortunei has negative impacts on this community, affecting the abundance and composition of species, and the size structure. The ability of the mussel to control the zooplankton can be explained by its direct consumption or by competition for trophic resources.